Conocimiento sobre etiquetado nutricional de alimentos procesados que se expende en la ciudad de Iquitos - Perez Rivera, Kackney Norma (2023)
The research was conducted in order to evaluate the knowledge of consumers about the nutritional labeling of foods sold in the city of Iquitos. The study was qualitative, non-experimental with a simple descriptive design. We worked with 385 people, obtained by random sampling the survey was used to collect data, ask a question and provide answer options. It was observed that 5.7% (n=22) never read, 31.7% (n=122) sometimes read and 19.5% (n=75) always read; 80.3% (n=309) have low knowledge level, 17.6% (n=68) medium and 2.1% (n=8) high. The choice of foods by the consumer considering the declaration and information in the nutritional labeling of foods, it was observed that 0.5% (n = 2) of them choose foods according to the statement on the label, 58.1% (n = 224) often get to choose and 5.5% (n = 21) always choose foods taking into account the declaration and information; demonstrated by empirical evidence with a confidence level of 95% that there is a low level of knowledge about the nutritional information of the labels of the foods sold in the city of Iquitos.